2019
DOI: 10.1002/cbf.3397
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin modulates intracellular signalling pathways that are critical for podocyte survival

Abstract: Damage to podocytes is a key event in glomerulopathies. While energy dense food can contribute to kidney damage, the role of the orixegenic hormone "ghrelin" in podocyte biology is still unknown. In the present study, we investigated the effect of ghrelin on podocyte survival as well as the signalling pathways mediating ghrelin effect in immortalized cultured rat podocytes. RT-PCR analysis revealed that GHS-R1 is expressed in rat podocytes. Western blot analysis showed that ghrelin upregulated COX-2 protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In the presence of IL-6, natural CD4 + T cells differentiate into Th17 cells (with TGF-α), instead of iTreg cells, which leads to a Th17/Treg cell imbalance. Research showed that high concentrations of IL-6 in sera and urine samples from SLE patients induced the degradation of Foxp3 and deregulation of Treg cells, possibly indicating a positive correlation with the severity of SLE [37,38]. Our previous studies suggested that a Th17/Treg imbalance was observed in the kidneys of LN mice, which resulted in increased levels of IL-6 and IL-17 and decreased concentration of Foxp3 [13].…”
Section: Discussionmentioning
confidence: 94%
“…In the presence of IL-6, natural CD4 + T cells differentiate into Th17 cells (with TGF-α), instead of iTreg cells, which leads to a Th17/Treg cell imbalance. Research showed that high concentrations of IL-6 in sera and urine samples from SLE patients induced the degradation of Foxp3 and deregulation of Treg cells, possibly indicating a positive correlation with the severity of SLE [37,38]. Our previous studies suggested that a Th17/Treg imbalance was observed in the kidneys of LN mice, which resulted in increased levels of IL-6 and IL-17 and decreased concentration of Foxp3 [13].…”
Section: Discussionmentioning
confidence: 94%
“…Ghrelin is an endogenous “brain-gut” peptide and is safe for humans. It could reduce apoptosis induced by various pathological stimuli, such as hydrogen peroxide and high glucose [ 14 , 26 , 27 ]. In this study, ghrelin significantly inhibited HG-induced cell oxidative stress and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Petri dishes were used to culture and treat MDA-MB-231 cells (2 × 10 5 cells/mL) with AELE (261 and 522 μg/ mL) for 24 h. The Qproteome mammalian protein prep kit (Qiagen, Hildren, Germany) was used to extract the proteins, which were then quantified based on the Lowry method. Proteins were prepared for separation by Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis (10%) as explained by El Zein et al [41], and transferred to Polyvinylidene fluoride membranes for protein assessment, as previously described [42]. Membranes were incubated with primary antibodies (1:1000) anti-cytochrome c (Abcam, Cambridge, UK), anti-p21 (Cell Signaling, Danvers, MA), anti-Bax and anti-Bcl2 (Elabscience, Houston, TX, USA).…”
Section: Western Blotmentioning
confidence: 99%